NILAI-NILAI PENDIDIKAN KARAKTER DALAM LIRIK TEMBANG DOLANAN - Setyaningsih (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Education today has been faced with the rampant phenomenon of moral degradation on the younger generation. Country that always puts the values of noble now already strats eroded by the attitude generation the nation's future. This phenomenon is a moral factor that is very detrimental to this nation. One of the ways to improve its slide  quality character is with known back the nation's cultures. Song Dolanan Javanese children feed one means culture able to change the character of the next generation of the Indonesian people . Javanese children's song development has national cultural values .  Unfortunately, song dolanan children Java language at the moment turtles got the right attention from government The instans-related. In the end, children are now less familiar with Javanese songs , so Javanese songs are less popular and eroded by time . This paper will be some a face about text implied in child dolanan Javanese song like the value - the value contained in Character Education. With a cargo of some aspects are indirectly song dolanan speaking children Java the noble values that are rooted in the culture of Indonesia esp usnya Java. In order to build national identity and character, Javanese children's songs need to be introduced to the young generation, especially the intestines of children. They are the relay holders of the journey of the life of the nation and state. When they lack understanding and experience of the potential of national culture and art it is feared that in the future this nation will lose its identity and noble character .